A wood-plastic composite board and its production process

By film-forming the surface of wood powder, and using film-forming agents such as modified alkyd resin and silicon sol to form a dense film layer, the problem of poor compatibility between wood and plastic is solved, and the mechanical properties of wood-plastic composite boards are significantly improved.

CN119144166BActive Publication Date: 2025-02-11GUANGDONG LIDA NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411620430.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-11
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Wood and plastic have poor compatibility when preparing wood-plastic composite boards, resulting in poor mechanical properties.

Method used

By pretreating the wood powder, the wood powder surface is film-formed using film-forming agents such as modified alkyd resin and silicon sol to form a dense and tough film layer to improve the compatibility between the wood powder and polyethylene.

Benefits of technology

The compatibility and mechanical properties of wood powder and polyethylene are improved, so that the prepared wood-plastic composite board has better dispersion stability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of wood-plastic composite materials, and specifically discloses a wood-plastic composite board and its production process. A wood-plastic composite board is made of the following raw materials in parts by weight: 50-60 parts of pretreated wood powder, 40-50 parts of polyethylene, 2-4 parts of antioxidant, and 1-3 parts of talcum powder. In the process of preparing the wood-plastic composite board, the present application pretreats the wood powder so that the compatibility of the wood powder and polyethylene is better, and the prepared wood-plastic composite board has the advantage of good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of wood-plastic composite materials, and more specifically, to a wood-plastic composite board and a production process thereof. Background Art

[0002] In recent years, as people's environmental awareness has gradually increased, the reuse of waste resources has received attention. Plastic products play an important role in people's production and life due to their good chemical stability and formability. However, as a high molecular polymer, plastic is difficult to degrade in the natural environment. If a large number of waste plastic products are not properly handled, they will exist in the soil, water and other environments for a long time, causing serious damage to the ecological environment. At the same time, the available forest resources are gradually scarce, but people's demand for wood is increasing. In order to realize the reuse of waste such as leftover scraps from wood processing and reduce the use of wood, wood-plastic composite panels came into being.

[0003] Wood-plastic composite board is a high-tech, green and environmentally friendly new decorative material made by mixing wood as the base material with plastic and processing aids, and then heating and extruding it through mold equipment.

[0004] Wood-plastic composite panels face an important problem during the production process, that is, the compatibility between wood and plastic is poor. Wood is mainly composed of cellulose, hemicellulose and lignin, and its surface contains a large number of polar groups such as hydroxyl groups, which is polar. However, there are almost no polar functional groups on the surface of plastic, which is non-polar. This difference between polarity and non-polarity leads to poor compatibility between wood and plastic. When wood and plastic are mixed to prepare wood-plastic composite panels, wood and plastic are prone to phase separation, making it difficult to form a uniform and stable wood-plastic composite panel, which in turn makes the mechanical properties of the wood-plastic composite panel poor. Therefore, it is necessary to solve the compatibility problem between wood and plastic.

[0005] The Chinese patent application document with publication number CN106987149A discloses a method for preparing an antistatic wood-plastic board. By adding a coupling agent during the preparation of the wood-plastic board, the problem of poor compatibility between the materials is solved, thereby maintaining or even enhancing the mechanical properties of the wood-plastic board.

[0006] The above patent application documents improve the compatibility of materials by adding coupling agents, but fail to fundamentally solve the incompatibility problem between wood and plastic, so the improvement of the compatibility of materials is very limited and the effect is weak. Summary of the invention

[0007] In order to further improve the compatibility of wood and plastic, and thus improve the mechanical properties of a wood-plastic composite board, the present application provides a wood-plastic composite board and a production process thereof.

[0008] In the first aspect, the present application provides a wood-plastic composite board, which adopts the following technical solution:

[0009] A wood-plastic composite board is made of the following raw materials in parts by weight: 50-60 parts of pretreated wood powder, 40-50 parts of polyethylene, 2-4 parts of antioxidant and 1-3 parts of talcum powder.

[0010] The preparation method of the pretreated wood powder comprises the following steps:

[0011] (1) Preparation of composite film-forming agent:

[0012] The modified alkyd resin and water are mixed evenly, and then silica sol and defoamer are added and mixed evenly to obtain a composite film-forming agent;

[0013] (2) Preparation of film-forming emulsion:

[0014] In a nitrogen atmosphere, polyethylene wax and maleic anhydride are mixed evenly, and an ether solution containing dibenzoyl peroxide is added to react. After the reaction is completed, octadecyl alcohol polyoxyethylene ether is added and mixed evenly, and then deionized water is added and mixed evenly, and vacuum rotary evaporation is performed to obtain a film-forming emulsion;

[0015] (3) One-step treatment of wood powder: Put the wood powder into a mixer and stir it, spray the composite film-forming agent in batches, stir and dry the treated wood powder to obtain one-step treated wood powder;

[0016] (4) Secondary treatment of wood powder: Place the primary treated wood powder in a blender and stir, spray the film-forming emulsion in batches, dry and crush the treated wood powder to obtain pretreated wood powder.

[0017] By adopting the above technical scheme, after the film-forming substance is coated on the surface of the wood powder, the interaction force between the wood powders is reduced, the agglomeration of the wood powders is prevented, and the dispersibility of the wood powders is improved; the smoothness of the wood powder surface is improved, the fluidity of the wood powder is increased, and the mixing of the wood powder and the polyethylene is made more uniform; after the film-forming substance is coated on the surface of the wood powder, the surface polarity of the wood powder is reduced, and the compatibility of the wood powder and the polyethylene is increased.

[0018] Preferably, in step (1), the preparation of the modified alkyd resin comprises the following steps: uniformly mixing soybean oil fatty acid, rosin, trimethylolpropane, terephthalic acid and pentaerythritol, heating to 180-190°C, keeping the temperature for 1-1.5h, then heating to 220-240°C, reacting for 120-140min, stopping heating, cooling to 170-180°C, adding trimellitic anhydride, reacting for 60-65min, cooling to 95-105°C, stopping nitrogen introduction, adding dimethylethanolamine, reacting for 13-18min, adding deionized water and stirring uniformly to obtain the modified alkyd resin.

[0019] By adopting the above technical scheme, the modified alkyd resin has better stability and can exist more stably on the surface of wood powder; and the surface of the prepared modified alkyd resin has a small amount of hydroxyl groups, which can better cooperate with the silica sol to form a film, enhance the toughness and stability of the silica sol film layer, make the silica sol film layer on the surface of the wood powder not easy to break, and improve the dispersion stability of the wood powder.

[0020] Preferably, in step (1), the mass percentage concentration of the silica sol is 20%-30%.

[0021] By adopting the above technical solution, during the film-forming process of silica sol, the silicon dioxide particles are evenly distributed, forming even protrusions on the surface of wood powder, and the formed film layer has high integrity and spreads evenly on the surface of wood powder; the film layer has high strength and is not easy to be damaged. The interaction force between wood powder is reduced, the dispersibility of wood powder is increased, the contact between the hydroxyl groups on the surface of wood powder and polyethylene is avoided, and the compatibility between wood powder and polyethylene is improved.

[0022] Preferably, in step (2), the mass ratio of polyethylene wax, stearyl alcohol polyoxyethylene ether and deionized water is 1:(0.14-0.18):(12-18).

[0023] By adopting the above technical scheme, the prepared film-forming emulsion has good leveling properties, and the formed wax film is dense, complete and has good flexibility, which reduces the resistance encountered by wood powder during movement, increases the fluidity of wood powder, and also improves the compatibility of wood powder and polyethylene.

[0024] Preferably, the mass ratio of the wood powder, the composite film-forming agent and the film-forming emulsion is (8-10):1:(1.1-1.3).

[0025] By adopting the above technical solution, the film layer formed on the surface of the wood powder has a moderate thickness and is uniform and complete, thereby enhancing the interfacial bonding force between the wood powder and the polyethylene. At the same time, the film layer on the surface of the wood powder has both good toughness and high strength, and is not easily broken due to shear stress during the mixing process, and the wood powder has good dispersion stability.

[0026] Preferably, the mass ratio of the rosin to the soybean oil fatty acid is (0.15-0.19):1.

[0027] By adopting the above technical scheme, the prepared modified alkyd resin has good stability and can form a denser and more stable film layer when synergistically forming a film with silica sol, which fully covers the wood powder particles and makes the wood powder have better dispersibility.

[0028] In a second aspect, the present application provides a production process for a wood-plastic composite board, comprising the following steps: placing pretreated wood powder, polyethylene, talcum powder, and an antioxidant into an internal mixer, internal mixing, discharging the materials into a mold, extruding, and demolding to obtain a wood-plastic board.

[0029] Preferably, the kneading temperature is 135-150°C.

[0030] By adopting the above technical solution, the polyethylene has better fluidity and can better wrap the pretreated wood powder particles, so that the two are fully in contact, the pretreated wood powder and the polyethylene are closely combined, and the compatibility of the two is improved; and the internal structure of the prepared wood-plastic composite board is uniform and complete, so that the wood-plastic composite board has good mechanical properties.

[0031] In summary, this application has the following beneficial effects:

[0032] 1. The surface hydroxyl groups of the modified alkyd resin produce hydrogen bonds with the silanol groups in the silica sol, and the modified alkyd resin and the silica sol produce a synergistic film-forming effect, which increases the flexibility and toughness of the silica sol film and makes the film layer not easy to break.

[0033] 2. Hydrogen bonds are easily formed between a large number of polar hydroxyl groups on the surface of wood powder. Wood powders have strong affinity and are easy to agglomerate. Polar hydroxyl groups have poor affinity with non-polar groups of plastics, and the interfacial bonding force between wood powder and plastics is weak. Film coating treatment is performed on the surface of wood powder to improve the dispersibility of wood powder and increase its compatibility with plastics.

[0034] 3. Physical interlocking increases the bonding strength with plastics; because alkyd resin melts at high temperatures, the surface film components of wood powder show a non-smooth state, the specific surface area increases, and the interfacial bonding strength with plastics is enhanced.

[0035] 4. Adding a small amount of rosin during the preparation of alkyd resin can enhance the thermal stability of alkyd resin and prevent it from decomposing easily at high temperature. After film formation, the excess hydroxyl groups on the surface of silica sol and alkyd resin react with the anhydride groups in the film-forming emulsion to undergo esterification reaction and are combined together through covalent bonds, thereby increasing the binding force between wood powder and plastic and enhancing the dispersibility of wood powder in plastic.

[0036] 5. Polyethylene wax and polyethylene have high compatibility. The compatibility of wood powder treated with polyethylene wax and polyethylene is improved. In the mixing process of wood powder and polyethylene, the wood powder is dispersed more evenly in polyethylene. After grafting, the anhydride groups on its surface react with the silica sol on the surface of the wood powder and the small amount of excess hydroxyl groups on the surface of the alkyd resin to undergo esterification reaction, and they are combined together through covalent bonds, which increases the binding force between the wood powder and the plastic, and enhances the dispersibility of the wood powder in the plastic.

[0037] 6. The dispersibility of wood powder increases, and the compatibility of wood powder and polyethylene increases, so that the prepared wood-plastic composite board has good mechanical properties. DETAILED DESCRIPTION

[0038] The present application is further described in detail below with reference to the embodiments.

[0039] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0040] Example 1

[0041] The wood-plastic composite board of this embodiment is made of the following raw materials: 50g of pretreated wood powder, 40g of polyethylene, 2g of antioxidant 1010, and 1g of talcum powder.

[0042] The method for preparing the pretreated wood powder of this embodiment comprises the following steps:

[0043] (1) Composite film-forming agent:

[0044] 37 g of modified alkyd resin, 58 g of silica sol with a mass percentage concentration of 20%, and 1 g of polyoxypropylene oxyethylene glycerol ether were mixed evenly to obtain a composite film-forming agent.

[0045] (2) Film-forming emulsion:

[0046] Add 20g of polyethylene wax and 2.5g of maleic anhydride to the reactor, introduce nitrogen, heat at 120°C for 20min, and after melting, heat to 150°C, use a feed pump to add 20g of 1% mass percent concentration of dibenzoyl peroxide ether solution to the reactor, the feed rate is 3.3mL / min, react for 1h after the feeding is completed, add 2.8g of octadecyl alcohol polyoxyethylene ether and mix evenly, then add 240g of deionized water and mix evenly, and evaporate under reduced pressure for 20min to obtain a film-forming emulsion.

[0047] (3) 320 g of wood powder was placed in a blender and stirred, and 40 g of the composite film-forming agent was sprayed into the blender 4 times, with the interval between each spraying being 2 min. The treated wood powder was stirred and dried to obtain a treated wood powder;

[0048] (4) The treated wood powder is placed in a blender and stirred, and 44 g of the film-forming emulsion is sprayed into the blender four times, with the time interval between each spraying being 2.5 min. The treated wood powder is dried and crushed to obtain pretreated wood powder.

[0049] The preparation of the modified alkyd resin of the present embodiment comprises the following steps:

[0050] 20g soybean oil fatty acid, 3g rosin, 20g trimethylolpropane, 35g terephthalic acid and 7.4g pentaerythritol were put into a reactor, nitrogen was introduced, heated and mixed evenly, the temperature was slowly raised to 180°C, kept warm for 60min, raised to 220°C, reacted for 120min, cooled to 170°C, 5.1g trimellitic anhydride was added, reacted for 60min, cooled to 95°C, the nitrogen was stopped, 10.4g dimethylethanolamine was added, reacted for 13min, 200g deionized water was added and stirred evenly to obtain a modified alkyd resin.

[0051] The preparation method of the wood-plastic composite board of this embodiment is as follows: 50g of pretreated wood powder, 40g of polyethylene, 1g of talcum powder, and 2g of antioxidant 1010 are put into an internal mixer and mixed evenly, heated to 135°C, internally kneaded for 15min, discharged into a mold, extruded at 70°C and 5MPa for 3min, and demolded to obtain a wood-plastic composite board.

[0052] Example 2

[0053] The wood-plastic composite board of this embodiment is made of the following raw materials: 60g of pretreated wood powder, 50g of polyethylene, 4g of antioxidant 1076, and 3g of talcum powder.

[0054] The method for preparing the pretreated wood powder of this embodiment comprises the following steps:

[0055] (1) Composite film-forming agent:

[0056] 42 g of modified alkyd resin, 63 g of silica sol with a mass percentage concentration of 30%, and 3 g of defoamer GP330 were mixed evenly to obtain a composite film-forming agent.

[0057] (2) Film-forming emulsion:

[0058] Add 15g of polyethylene wax and 1.9g of maleic anhydride to the reactor, introduce nitrogen, heat at 120°C for 20min, and after melting, heat to 150°C, use a feed pump to add 15g of 1% mass percent concentration of dibenzoyl peroxide ether solution to the reactor, the feed rate is 2.5mL / min, react for 1h after the feeding is completed, add 2.7g of octadecyl alcohol polyoxyethylene ether and mix evenly, then add 270g of deionized water and mix evenly, and evaporate under reduced pressure for 20min to obtain a film-forming emulsion.

[0059] (3) 400 g of wood powder was placed in a blender and stirred, and 40 g of the composite film-forming agent was sprayed into the blender 5 times, with the time interval between each spraying being 2.5 min. The treated wood powder was stirred and dried to obtain a treated wood powder;

[0060] (4) The treated wood powder is placed in a blender and stirred, and 52 g of the film-forming emulsion is sprayed into the blender five times, with the time interval between each spraying being 3 minutes. The treated wood powder is dried and crushed to obtain pretreated wood powder.

[0061] The preparation of the modified alkyd resin of the present embodiment comprises the following steps:

[0062] 20g soybean oil fatty acid, 3.8g rosin, 22g trimethylolpropane, 38g terephthalic acid and 7.4g pentaerythritol were put into a reactor, nitrogen was introduced, heated and mixed evenly, the temperature was slowly raised to 190°C, kept warm for 90min, then raised to 240°C, reacted for 140min, cooled to 180°C, 5g trimellitic anhydride was added, reacted for 65min, cooled to 105°C, the introduction of nitrogen was stopped, 10.5g dimethylethanolamine was added, reacted for 18min, 200g deionized water was added and stirred evenly to obtain a modified alkyd resin.

[0063] The preparation method of the wood-plastic composite board of this embodiment is as follows: 60g of pretreated wood powder, 50g of polyethylene, 4g of talcum powder, and 4g of antioxidant 1076 are put into an internal mixer and mixed evenly, the temperature is raised to 150°C, and the internal mixer is kneaded for 15min. The material is discharged into a mold, extruded at 70°C and 5MPa for 3min, and demolded to obtain a wood-plastic composite board.

[0064] Example 3

[0065] The wood-plastic composite board of this embodiment is made of the following raw materials: 52g of pretreated wood powder, 45g of polyethylene, 1g of antioxidant 626, 1.5g of antioxidant 1010, and 1.2g of talcum powder.

[0066] The method for preparing the pretreated wood powder of this embodiment comprises the following steps:

[0067] (1) Composite film-forming agent:

[0068] 40 g of modified alkyd resin, 62 g of silica sol with a mass percentage concentration of 28%, and 2 g of TEGO-825 defoamer were mixed evenly to obtain a composite film-forming agent.

[0069] (2) Film-forming emulsion:

[0070] Add 20g of polyethylene wax and 2.7g of maleic anhydride to the reactor, introduce nitrogen, heat at 120°C for 20min, and after melting, heat to 150°C, use a feed pump to add 20g of 1% mass percent concentration of dibenzoyl peroxide ether solution to the reactor, the feed rate is 3.3mL / min, react for 1h after the feeding is completed, add 3g of octadecyl alcohol polyoxyethylene ether and mix evenly, then add 340g of deionized water and mix evenly, and evaporate under reduced pressure for 20min to obtain a film-forming emulsion.

[0071] (3) 360 g of wood powder was placed in a blender and stirred, and 40 g of the composite film-forming agent was sprayed into the blender three times, with the time interval between each spraying being 3 min. The treated wood powder was stirred and dried to obtain a treated wood powder;

[0072] (4) The treated wood powder is placed in a blender and stirred, and 48 g of the film-forming emulsion is sprayed into the blender four times, with the time interval between each spraying being 3 minutes. The treated wood powder is dried and crushed to obtain pretreated wood powder.

[0073] The preparation of the modified alkyd resin of the present embodiment comprises the following steps:

[0074] 20g soybean oil fatty acid, 3.5g rosin, 19g trimethylolpropane, 35g terephthalic acid and 11g pentaerythritol were put into a reactor, nitrogen was introduced, heated and mixed evenly, the temperature was slowly raised to 183°C, kept warm for 65min, raised to 225°C, reacted for 130min, cooled to 172°C, 5.1g trimellitic anhydride was added, reacted for 62min, cooled to 100°C, the nitrogen was stopped, 10.5g dimethylethanolamine was added, reacted for 15min, 200g deionized water was added and stirred evenly to obtain a modified alkyd resin.

[0075] The preparation method of the wood-plastic composite board of this embodiment is as follows: 52g of pretreated wood powder, 45g of polyethylene, 2.5g of talcum powder, 1g of antioxidant 626, and 1.5g of antioxidant 1010 are put into an internal mixer and mixed evenly, the temperature is raised to 145°C, and the internal mixer is kneaded for 15min. The material is discharged into a mold, extruded at 70°C and 5MPa for 3min, and demolded to obtain a wood-plastic composite board.

[0076] Comparative Example 1

[0077] The wood-plastic composite board of this comparative example is made of the following raw materials: 50g of pretreated wood powder, 40g of polyethylene, 2g of antioxidant 1010, and 1g of talcum powder.

[0078] The preparation method of the pretreated wood powder of this comparative example comprises the following steps:

[0079] (1) Film-forming emulsion:

[0080] Add 20g of polyethylene wax and 2.5g of maleic anhydride to the reactor, introduce nitrogen, heat at 120°C for 20min, and after melting, heat to 150°C, use a feed pump to add 20g of 1% mass percent concentration of dibenzoyl peroxide ether solution to the reactor, the feed rate is 3.3mL / min, react for 1h after the feeding is completed, add 2.8g of octadecyl alcohol polyoxyethylene ether and mix evenly, then add 240g of deionized water and mix evenly, and evaporate under reduced pressure for 20min to obtain a film-forming emulsion.

[0081] (2) 320 g of wood powder was placed in a blender and stirred, and 40 g of silica sol having a mass percentage concentration of 20% was sprayed into the blender four times, with the time interval between each spraying being 2 min. The treated wood powder was stirred and dried to obtain a treated wood powder;

[0082] (3) The treated wood powder is placed in a blender and stirred, and 44 g of the film-forming emulsion is sprayed into the blender four times, with the time interval between each spraying being 2.5 min. The treated wood powder is dried and crushed to obtain pretreated wood powder.

[0083] The preparation method of the wood-plastic composite board of this comparative example is as follows: 50g pretreated wood powder, 40g polyethylene, 1g talcum powder, and 2g antioxidant 1010 are put into an internal mixer and mixed evenly, the temperature is raised to 135°C, and the internal mixer is kneaded for 15min. The material is discharged into a mold, extruded at 70°C and 5MPa for 3min, and demolded to obtain a wood-plastic composite board.

[0084] Comparative Example 2

[0085] The wood-plastic composite board of this comparative example is made of the following raw materials: 50g of pretreated wood powder, 40g of polyethylene, 2g of antioxidant 1010, and 1g of talcum powder.

[0086] The preparation method of the pretreated wood powder of this comparative example comprises the following steps:

[0087] (1) Film-forming emulsion:

[0088] Add 20g of polyethylene wax and 2.5g of maleic anhydride to the reactor, introduce nitrogen, heat at 120°C for 20min, and after melting, heat to 150°C, use a feed pump to add 20g of 1% mass percent concentration of dibenzoyl peroxide ether solution to the reactor, the feed rate is 3.3mL / min, react for 1h after the feeding is completed, add 2.8g of octadecyl alcohol polyoxyethylene ether and mix evenly, then add 240g of deionized water and mix evenly, and evaporate under reduced pressure for 20min to obtain a film-forming emulsion.

[0089] (2) 320 g of wood powder was placed in a mixer and stirred, and 40 g of modified alkyd resin was sprayed into the mixer four times, with the time interval between each spraying being 2 min. The treated wood powder was stirred and dried to obtain a treated wood powder;

[0090] (3) The treated wood powder is placed in a blender and stirred, and 44 g of the film-forming emulsion is sprayed into the blender four times, with the time interval between each spraying being 2.5 min. The treated wood powder is dried and crushed to obtain pretreated wood powder.

[0091] The preparation of the modified alkyd resin of this comparative example comprises the following steps:

[0092] 20g soybean oil fatty acid, 3g rosin, 20g trimethylolpropane, 35g terephthalic acid and 7.4g pentaerythritol were put into a reactor, nitrogen was introduced, heated and mixed evenly, the temperature was raised to 180°C, kept warm for 60min, raised to 220°C, reacted for 120min, cooled to 170°C, 5.1g trimellitic anhydride was added, reacted for 60min, cooled to 95°C, the nitrogen was stopped, 10.4g dimethylethanolamine was added, reacted for 13min, 200g deionized water was added and stirred evenly to obtain a modified alkyd resin.

[0093] The preparation method of the wood-plastic composite board of this comparative example is as follows: 50g pretreated wood powder, 40g polyethylene, 1g talcum powder, and 2g antioxidant 1010 are put into an internal mixer and mixed evenly, the temperature is raised to 135°C, and the internal mixer is kneaded for 15min. The material is discharged into a mold, extruded at 70°C and 5MPa for 3min, and demolded to obtain a wood-plastic composite board.

[0094] Comparative Example 3

[0095] The wood-plastic composite board of this comparative example is made of the following raw materials: 50g of pretreated wood powder, 40g of polyethylene, 2g of antioxidant 1010, 1g of talcum powder, and 1g of polyethylene wax.

[0096] The preparation method of the pretreated wood powder of this comparative example comprises the following steps:

[0097] (1) Composite film-forming agent:

[0098] 37 g of modified alkyd resin, 58 g of silica sol with a mass percentage concentration of 20%, and 1 g of polyoxypropylene oxyethylene glycerol ether were mixed evenly to obtain a composite film-forming agent.

[0099] (2) 320 g of wood powder was placed in a blender and stirred. 40 g of the composite film-forming agent was sprayed into the blender four times with a time interval of 2 min between each spraying. The treated wood powder was stirred and crushed to obtain pretreated wood powder.

[0100] The preparation of the modified alkyd resin of this comparative example comprises the following steps:

[0101] 20g soybean oil fatty acid, 3g rosin, 20g trimethylolpropane, 35g terephthalic acid and 7.4g pentaerythritol were put into a reactor, nitrogen was introduced, heated and mixed evenly, the temperature was slowly raised to 180°C, kept warm for 60min, raised to 220°C, reacted for 120min, cooled to 170°C, 5.1g trimellitic anhydride was added, reacted for 60min, cooled to 95°C, the nitrogen was stopped, 10.4g dimethylethanolamine was added, reacted for 13min, 200g deionized water was added and stirred evenly to obtain a modified alkyd resin.

[0102] The preparation method of the wood-plastic composite board of this comparative example is as follows: 50g of pretreated wood powder, 40g of polyethylene, 1g of talcum powder, 2g of antioxidant 1010, and 1g of polyethylene wax are put into an internal mixer and mixed evenly, heated to 135°C, internally kneaded for 15min, discharged into a mold, extruded at 70°C and 5MPa for 3min, and demolded to obtain a wood-plastic composite board.

[0103] Performance testing

[0104] The performance testing methods of wood-plastic composite panels are as follows:

[0105] 1. Tensile performance test

[0106] The tensile properties test method of wood-plastic composite panels refers to the national standard GB / T1040-92, the sample thickness is 4mm, and the test speed is 5mm / min.

[0107] 2. Bending performance test

[0108] The bending performance test method of wood-plastic composite panels refers to the national standard GB / T9341-2008, the sample length is 80mm, the sample width is 10mm, the sample thickness is 4mm, and the test speed is 2mm / min.

[0109] 3. Impact performance test

[0110] The impact performance test method of wood-plastic composite panels refers to the national standard GB / T1043.1-2008, with a sample length of 80 mm, a sample width of 10 mm, a sample thickness of 4 mm, and a span of 62 mm.

[0111] The performance test data of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in Table 1 below:

[0112] Table 1 Test data

[0113]

[0114] It can be seen from the analysis of Examples 1-3 and Comparative Examples 1-3 in combination with Table 1 that the mechanical properties of the wood-plastic composite board can be improved by pretreating the wood powder with the composite film-forming agent and the film-forming emulsion.

[0115] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A wood-plastic composite board, characterized in that: The method is prepared from the following raw materials in parts by weight: 50-60 parts of pretreated wood powder, 40-50 parts of polyethylene, 2-4 parts of antioxidant, and 1-3 parts of talc; The preparation method of the pretreated wood powder comprises the following steps: (1) Preparation of composite film-forming agent: The modified alkyd resin and water are mixed evenly, and then silica sol and defoamer are added and mixed evenly to obtain a composite film-forming agent; The preparation of the modified alkyd resin comprises the following steps: uniformly mixing soybean oil fatty acid, rosin, trimethylolpropane, terephthalic acid and pentaerythritol, heating to 180-190° C., keeping the temperature for 1-1.5 hours, then heating to 220-240° C., reacting for 120-140 minutes, stopping heating, cooling to 170-180° C., adding trimellitic anhydride, reacting for 60-65 minutes, cooling to 95-105° C., stopping nitrogen introduction, adding dimethylethanolamine, reacting for 13-18 minutes, adding deionized water and stirring uniformly to obtain the modified alkyd resin; (2) Preparation of film-forming emulsion: In a nitrogen atmosphere, polyethylene wax and maleic anhydride are mixed evenly, and an ether solution containing dibenzoyl peroxide is added to react. After the reaction is completed, octadecyl alcohol polyoxyethylene ether is added and mixed evenly, and then deionized water is added and mixed evenly, and vacuum rotary evaporation is performed to obtain a film-forming emulsion; (3) One-step treatment of wood powder: Put the wood powder into a mixer and stir it, spray the composite film-forming agent in batches, stir and dry the treated wood powder to obtain one-step treated wood powder; (4) Secondary treatment of wood powder: Place the primary treated wood powder in a blender and stir, spray the film-forming emulsion in batches, dry and crush the treated wood powder to obtain pretreated wood powder.

2. A wood-plastic composite board according to claim 1, characterized in that: In the step (1), the mass percentage concentration of the silica sol is 20%-30%.

3. The wood-plastic composite board according to claim 1, characterized in that: In the step (2), the mass ratio of polyethylene wax, octadecyl alcohol polyoxyethylene ether and deionized water is 1:(0.14-0.18):(12-18).

4. The wood-plastic composite board according to claim 1, characterized in that: The mass ratio of the wood powder, the composite film-forming agent and the film-forming emulsion is (8-10):1:(1.1-1.3).

5. The wood-plastic composite board according to claim 1, characterized in that: The mass ratio of the rosin to soybean oil fatty acid is (0.15-0.19):

1.

6. A production process for a wood-plastic composite board as claimed in claim 1, characterized in that: The method comprises the following steps: putting pretreated wood powder, polyethylene, talcum powder and antioxidant into an internal mixer, internal mixing, discharging the materials into a mold, extruding, demoulding and obtaining a wood-plastic board.

7. The production process of a wood-plastic composite board according to claim 6, characterized in that: The temperature of the banburying is 135-150°C.

Citation Information

Patent Citations

  • Preparation method of anti-static wood plastic

    CN106987149A

  • Alkyd resin composition comprising silica

    CA2859765A1

  • Preparation method of silica sol surface modified straw wood-plastic composite material

    CN102850815A